Polityka informacyjna i dostęp do dokumentów w instytucjach Unii Europejskiej - Jurga-Wosik, Ewa (Przegląd Politologiczny, 2018)
The issue of access to information and documents concerning the functioning of European Union institutions is extensive and complex. It encompasses all activities to promote or pro- vide citizens with information on the operation of European Union institutions, and in particu- lar the access to European Union materials, which is regulated by numerous separate provisions. The most important ones involve the principles behind the publishing of EU mate- rials and legal regulations on access to documents that have not been published and those sent to the archives. Consequently, there are separate regulations on information policy and the right to access documents. The author counterpoints the legal foundations for access to EU documents with the practical execution of this right and fulfillment of the provisions of EU in- formation policy.